A new wine tasting approach based on emotional responses to rapidly recognize classic european wine styles - Loureiro, Virgilio (2019)
Conventional tasting sheets are widely used to evaluate wine quality in wine tasting competitions. However, the higher scores are mostly obtained by international commercial wines, resulting in lower scores being awarded to the classic Europeanwines. We hypothesize that this is due to the tasting methodology that fails to recognize this wine style. Therefore, the purpose of this work was to show the implementation of a new wine tasting approach to overcome this drawback. The proposed training technique is based on the emotional responses of the taster after smelling two wines of clearly opposite styles. The first wine is characterized by high aromatic intensity but low in-mouth intensity, perceived as disappointing to the taster, here defined as an “easy” wine. The second wine is characterized as a wine with low aromatic intensity but that provides an unexpectedly positive in-mouth experience, here defined as a “difficult” wine. These emotions are explained by the wine sensorial characteristics. The “easy” wine has an intense, simple smell with short persistence while the “difficult” wine has a low intensity, complex aroma, and long persistence. The first style corresponds to the international commercial wines most prized in international wine challenges. The second, frequently rejected by untrained tasters, is consistent with the “so called” classic European wines, and is characterized by light red or yellow straw colors, weak smell intensity, and aggressive mouth-feel. After no more than four training sessions and using the OIV tasting sheet, inexperienced tasters were able to score “difficult” wines equally as “easy” wines and understand their different attributes. In conclusion, this new tasting approach may be used by wine professionals to explain the characteristics of high quality wines that are not easily recognized by untrained consumers